Mistreatment and Its Associated Factors among Women during Labor and Delivery in Hospitals of Silte Town, Southern Ethiopia - Hassen Halil; Ayanos Benti; Yonas Zeleke; Ritbano Abdo (Mashhad University of Medical Sciences, 2020)
Background & aim: Current evidence clearly shows that the mistreatment of women during labor and childbirth in health facilities is on the rise all over the world. This kind of disrespectful treatment deters women from seeking care. In spite of this, little attention has been devoted to this critical issue both in practice and research. With this background in mind, the current study aimed to investigate the prevalence of mistreatment and its associated factors among women during labor and childbirth in public hospitals of Silte Town, Southern Ethiopia. Methods: This hospital-based cross-sectional study was carried out on 409 participants using the systematic sampling method within March 1-30, 2018. The data collection was performed using a structured instrument. The data were entered into EpiData software (version 3.1) and analyzed in SPSS software (version 23). Binary logistic regression analyses were computed to identify the associated factors at 95% CI. Results: The overall prevalence of mistreatment was observed to be 67.7%. The factors which were significantly associated with the mistreatment included complicated labor (AOR=2.6; 95%CI: 1.07-6.06) and a longer stay at a health facility (AOR=2.6; 95% CI: 1.34-5.18). On the other hand, having antenatal care visits (AOR=0.5; 95% CI: 0.4-0.79) and the existence of birth companion during childbirth (AOR=0.35; 95% CI: 0.21-0.57) were found to be protective factors of mistreatment. Conclusion: Mistreatment during childbirth and labor is still a serious public concern in the study area. Therefore, all the responsible bodies must develop efficient methods for the prevention and elimination of mistreatment. To this end, they need to strengthen the continuous provision of antenatal care education and counseling, allow for the presence of birth companions, and minimize unnecessarily long health facility stays after childbirth.